Zn nutrients-loaded chitosan nanocomposites and their efficacy as nanopriming agents for maize (Zea mays) seeds - Zungu, Bongiwe; Kamdem Paumo, Hugues; Gaorongwe, Joseph Lesibe; Tsuene, Gaborone Neo; Ruzvidzo, Oziniel; Katata-Seru, Lebogang (Frontiers in Chemistry, 2023)
Recent breakthroughs in agro-inputs research have led to the development of nanomaterials that can promote precision agriculture and better environmental security. The agricultural sector is increasingly facing the negative impacts of changing climates due to various stress conditions. To curb this scenario, economical and low-risk practices such as decreasing fertilizer inputs and seed priming have been promoted. In the current study, the H. odoratissimum aqueous extract was used to nucleate the Zn ionic species and grow the zinc oxide nanoparticles (ZnO NPs). The developed nanocomposites and their ionic zinc precursor were then integrated into tripolyphosphate (TPP)-crosslinked chitosan (CS/TPP) nanostructures by ionic gelation. Advanced physicochemical characterization techniques (SEM, EDS, TEM, DLS, FTIR, TGA, and XPS) were exploited to report the morphology, hydrodynamic size, surface charge, and structural organization of the developed nanomaterials. These revealed positively charged particles with hydrodynamic size in the 149–257 nm range. The NPs were used as priming agents for Zea mays seeds. At 0.04%, the ZnO-loaded CS/TPP NPs achieved higher root and shoot elongation in 10-day old seedlings compared to other treatments. The pristine CS/TPP NPs, Zn(II)-laden CS/TPP NPs, and ZnO-loaded CS/TPP NPs at 0.01% significantly promoted the early seedling development of seeds under salt stress. This represents the first report showing ZnO integrated chitosan nanocomposites as an auspicious nanopriming agent for stimulating the seed germination of maize. The study envisages offering perspectives on utilizing green nanotechnology to improve the early seedling development of maize. Furthermore, it has the potential to contribute towards UN SDG 2, thus addressing the threats to global food insecurity and doubling agricultural productivity by 2030.